Three new species of Sarcocornia (Chenopodiaceae) from South Africa - Mucina, Ladislav; Steffen, S.; Kadereit, G. (2009)
Intensive field studies and collection of specimens conducted from 2000 to 2006 were aimed at the description of vegetation of saline habitats of southern Africa (Mucina et al. 2006a – c). This also set the basis for a systematic and biogeographical study of South African Sarcocornia (Steffen 2006), which is a prominent floristic element of hygrohalophytic habitats worldwide. Our molecular phylogenetic studies based on ETS and chloroplast-genome sequences and our intensive morphological survey of the genus (Steffen et al. 2007, Steffen et al. in press) revealed that Sarcocornia A. J. Scott contains two species not recognised in older revisions by Moss (1954), Tölken (1967) and O’Callaghan (1992). Furthermore, a third species is proposed to be newly described here. The known collections pertinent to this taxon had been previously considered to represent Sarcocornia perennis (Mill.) A. J. Scott, a species well-known from Eurasia (e.g. Moss 1954; Tölken 1967; O’Callaghan 1992; Davy et al. 2006). Despite its morphological and ecological similarity to the Eurasian S. perennis, detailed morphological investigations revealed differences, mainly in seed morphology. A recent molecular-phylogenetic analysis of the Salicornioideae (Kadereit et al. 2006) showed that S. perennis is clearly diphyletic and that the southern African “S. perennis” (sensu auctorum austroafricanum) represents an independent evolutionary entity.